Severe acute maternal morbidity: study of epidemiology and risk factors - Sinha, Mridu; Goel, J. K.; Sah, Shanti; Goel, Ruchica; Chaurasia, Rajani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: For last decade, severe acute maternal morbidity (SAMM) has emerged as a promising alternative to maternal mortality reviews. Maternal mortality may represent the tip of iceberg whose large base is formed by SAMM. The objective was to study the cases of critically ill obstetric i.e. pregnant and puerperal patients requiring intensive care due to severe acute maternal morbidity (near miss cases) and to analyze the common preventable risk factors associated with them. Methods: This is a retrospective cohort study of women admitted during pregnancy or within 6 weeks postpartum, to multidisciplinary intensive care unit (ICU) of a tertiary-care teaching hospital, Sri Ram Murti Smarak Institute of Medical Sciences, Bareilly, UP, India, from April 2013 to April 2016. The data was collected pertaining to demographics, obstetric history, any pre-existing medical illness, reasons for admission to ICU, treatment given and their outcome in terms of maternal morbidity and mortality. Results: The study found the prevalence of SAMM to be 1.87%. The average age of admission was 26.6 years and most were primigravidas (42%), unbooked (97%) coming from rural areas (75%). The most common obstetric cause of ICU admission was hypertensive disorders of pregnancy and the most common non-obstetric cause was sepsis. Maternal mortality index was 25.8% and fetal mortality rate was 257 per 1000 births among SAMM cases. Conclusions: Study of risk factors associated with SAMM can provide important contributions to improve quality of available health care system in order to achieve reduction in maternal mortality.